EFFECTIVENESS OF PONTIANAK CITY GOVERNMENT INNOVATION POLICY BISNIS CAKEP LALU LINTAS LANCAR AND GOVERNMENT AND SMART CITY LANDMARK - Ul Qadri; Verdico Arief (Journal Ilmu Sosial, Politik, dan Ilmu Pemerintahan, 2018)
Pontianak is one of the regions that get appreciation from the Government of the Republic Indonesia on various creation innovation program policy in public administration sector. Among the products in the field of innovation is the application bisnis cakep lalu lintas lancar (BCL) and application government and smart city landmark (Gencil). Both applications are used Pontianak City Government to manage the government and public service. All policies or programs implemented by the government must be effective. However, to produce a product effectiveness of a policy or program should do some research. For that we need research that focuses in measuring about how effectiveness of Pontianak City government innovation policy bisnis cakep lalu lintas lancar and government and smart city landmark. This research is conducted qualitatively with the aim to find and search data and information in depth related to how big the effectiveness of product created. Thus will be known how the level of effectiveness of a policy or program that has been implemented by the government of Pontianak City.